Religious Nationalism in the 21st Century - Zubrzycki, Geneviève (Sociology of religion, 2025)
Religious nationalism is one of the most significant political phenomena of the past decades, mobilizing large numbers of people across the globe. This article examines how religious nationalism has been conceptualized in the literature on nationalism and discusses what the sociology of religion has to offer to understand and explain the phenomenon.